Brunner's Gland Hamartomas: Two Cases of This (Sometimes) Distinctive Lesion. Issue 9 (28th August 2021) - Bush, Allison; Francis, Jonathan; Laczek, Jeffrey
Abstract: Brunner's gland hamartomas (BGHs) are rare, benign, primary duodenal tumors. The clinical presentations can vary, and confirming a diagnosis can be challenging because of the submucosal nature of the lesions. We report two cases of BGHs with different clinical presentations. The diagnoses were not determined initially, despite utilizing endoscopy, mucosal biopsies, endoscopic ultrasound, and, in one case, fine-needle aspiration. Confirmation of BGHs was subsequently made following endoscopic or surgical resection.